(3x+20)=x

Simple and best practice solution for (3x+20)=x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3x+20)=x equation:


Simplifying
(3x + 20) = x

Reorder the terms:
(20 + 3x) = x

Remove parenthesis around (20 + 3x)
20 + 3x = x

Solving
20 + 3x = x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
20 + 3x + -1x = x + -1x

Combine like terms: 3x + -1x = 2x
20 + 2x = x + -1x

Combine like terms: x + -1x = 0
20 + 2x = 0

Add '-20' to each side of the equation.
20 + -20 + 2x = 0 + -20

Combine like terms: 20 + -20 = 0
0 + 2x = 0 + -20
2x = 0 + -20

Combine like terms: 0 + -20 = -20
2x = -20

Divide each side by '2'.
x = -10

Simplifying
x = -10

See similar equations:

| x-4+5-y= | | -3x+7=43 | | 8(t-6)+4=4(3t+5)-9 | | ln(8+x)=3 | | 3x-4(c-5)-2(y-6)= | | (-4r^3)(8r^2+7)(8r^2-7)= | | (4b-5f)(4b+4f)= | | (9-u)(5+5u)= | | (3x+6)(2x+3)= | | (4x+7)(4x-5)= | | 30x^3+51x^2-60x= | | (r+4)(r-2)= | | (5t^2-t-5)(2t^2+5t-1)= | | (x^3+x^2+x+1)(15x-4)= | | (9x+4)(6x^2+9x+5)= | | 9x^2(x^2+6xy-7y^2)= | | (9x^2)(x^2+6xy-7y^2)= | | (4x^3)(2x^2-4x+4)= | | 4x^3(2x^2-4x+4)= | | (5x)*(-9x^3+6x^2)= | | (5x+3)=(3x-7) | | .30*80+.60x=.40*80+.40x | | 50=(3x-1) | | 3a+7a= | | 0.36(18)+0.06x=0.12(6+x) | | (10x+11)=39+40 | | 4(x+1)=2(2x+7)-10 | | x-(4-2x)=7(x-1) | | 5x-2(x-7)=14 | | 2(3x-4)=3x-14 | | 2x^2+3x-16x-7=0 | | y=7x+18 |

Equations solver categories